The mediated construction of reality - Couldry, Nick; Hepp, Andreas (Polity Press, 2016)
"Social theory needs to be radically rethought for a world of digital media and social media platforms driven by data processes. Fifty years after Berger and Luckmann published their classic text, The Social Construction of Reality, two leading sociologists of media, Nick Couldry and Andreas Hepp, revisit the question of how the social world is constructed -- that is, made -- by human beings. What difference does the deep involvement of digital media, and the data processes on which they rely, make to the type of social world we can inhabit? And how should we evaluate the consequences for our quality of life? Drawing on a range of theory and a wide selection of empirical studies, this book offers an authoritative account of how the digital world has historically emerged, and where it is now heading." -- Provided by publisher